The Influence of Product Quality, Live Shopping Service Quality, and Consumer Trust on Wardah Product Purchasing Decisions by Generation Z - Jovanka Rizki Utami; Widarta Widarta (LifeSciFi, 2025)
This study aims to analyze the influence of product quality, live shopping service quality, and consumer trust on Wardah product purchasing decisions by Generation Z through the Shopee e-commerce platform in Yogyakarta. In the digital context, consumer trust, in addition to product quality, is a key factor in determining online purchasing behavior. This study used a quantitative approach with 100 respondents selected through a purposive sampling technique. The research instrument was a closed-ended questionnaire with a five-point Likert scale, and the data were analyzed using multiple linear regression. The results showed that product quality and consumer trust had a significant partial effect on purchasing decisions, while live shopping service quality had no significant effect. However, simultaneously, the three variables had a significant effect with an Adjusted R² value of 0.603, meaning 60.3% of the variation in purchasing decisions can be explained by this model. These findings emphasize the importance of a holistic approach in digital marketing strategies, emphasizing product quality, building trust, and increasing the effectiveness of live shopping services to encourage consumer loyalty in the e-commerce era.